Business Coaching & Mentoring - Taylor, Marie, author; Crabb, Steve (Business coach), author (Hoboken, NJ : dummies, A Wiley Brand, 2017)
Navigating the world of coaching and mentoring -- Making the case for coaching and mentoring -- Developing the skills and knowledge base of a coach and mentor -- Assessing clients' needs before coaching -- Managing the inner world of thoughts and emotions -- Helping leaders recognize why "I did it my way" isn't the best epitaph -- Coaching clients through their blind spots -- Telling a compelling story in business -- Helping clients to assess their own business objectively -- Developing vision, mission, and values -- Transforming visions into workable plans -- Mentoring for personal success and empowering leadership -- Developing the brand of you -- Developing relationships at all levels -- Coaching the help business engage, inform, and influence -- Ten online resources to boost coaching and mentoring effectiveness -- Ten tips for leaders who coach or mentor people in business -- Ten tips for business leaders hiring a business coach -- Ten questions to keep a business on track.